1999
DOI: 10.1007/bf02376000
|View full text |Cite
|
Sign up to set email alerts
|

Self-diffusion in α-Fe2O3 natural single crystals

Abstract: Measurements of 180 self-diffusion in hematite (Fe203) natural single crystals have been carried out as a function of temperature at constant partial pressure ao2 = 6.5"10 -2 in the temperature range 890 to 1227 ~ The ao2 dependence of the oxygen self-diffusion coefficient at fixed temperature T = 1150 ~ has also been deduced in the ao2 range 4.5" 10 .4 -6.5" 10 1. The concentration profiles were established by secondary-ion mass spectrometry; several profiles exhibit curvatures or long tails; volume diffusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 21 publications
6
63
0
Order By: Relevance
“…This is accomplished through an oxidation process, which offers new sites for accommodation of the excess Fe 3+ cations. The empty sites in the oxygen sublattice serve as the pathways for cation migration, as shown by Fe selfdiffusion studies (Amami et al 1999;Sabioni et al 2005;Hallström et al 2011). It has been demonstrated that at higher temperatures, the diffusion of Fe along the c-axis of (10)…”
Section: Discussionmentioning
confidence: 99%
“…This is accomplished through an oxidation process, which offers new sites for accommodation of the excess Fe 3+ cations. The empty sites in the oxygen sublattice serve as the pathways for cation migration, as shown by Fe selfdiffusion studies (Amami et al 1999;Sabioni et al 2005;Hallström et al 2011). It has been demonstrated that at higher temperatures, the diffusion of Fe along the c-axis of (10)…”
Section: Discussionmentioning
confidence: 99%
“…O tracer diffusion reveal that oxygen diffusion is faster than that of Fe [169]. In general it seems that both V O and interstitial Fe can form, but Catlow et al [172] proposed that electronic disorder far outweighs ionic diffusion and is responsible for electric conductivity.…”
mentioning
confidence: 99%
“…Consequently, even when high-quality crystals free of apparent cracks and inclusions are chosen for lattice diffusion studies, contributions from ''fast-paths'' may be observed in the form of diffusion profiles exhibiting ''tails'' (Reddy and Cooper, 1982;Cawley et al, 1991;Watson and Cherniak, 1997;Moore et al, 1998;Amami et al, 1999). These ''tailed'' diffusion profiles are evidence that there exists another diffusion pathway besides the crystal lattice.…”
Section: Introductionmentioning
confidence: 95%
“…Because they used a mathematical model for polycrystalline materials with grain boundaries to fit their data, they made the assumption that the fast-paths are like grain boundaries, even though this assumption was not explicitly stated in their papers. Several similar treatments later appeared, for example for oxygen diffusion in corundum , and oxygen diffusion in hematite (Amami et al, 1999). However, the authors did not discuss in detail their assumptions and reasons for selecting these models.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation